Strategic Empowerment of Millennial Farmers for Achieving Sustainable Agriculture in the Digital Era - Kurnia Hidayatispi; Amir Lababa (CV. HEI PUBLISHING INDONESIA, 2025)
The regeneration crisis, reflected in the declining proportion of young farmers in the 2023 Agricultural Census, poses a serious threat to Indonesia’s food security and agricultural innovation capacity. This study aims to examine the causal influence of the 3 Pillar Digital Agripreneurship Empowerment Model—comprising Digitalization, Entrepreneurship, and Institutional Support—on the agricultural sustainability of millennial farmers in three pilot provinces. An explanatory quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a sample of N = 350 respondents, and both the measurement and structural models were rigorously evaluated. The results indicate that the 3-Pillar Model explains 64.5% of the variance in agricultural sustainability (R² = 0.645). The Entrepreneurship Pillar shows the strongest effect (β = 0.421, p < 0.001), followed by the Digitalization Pillar (β = 0.387, p < 0.001), while Institutional Support remains statistically significant but exhibits the weakest influence (β = 0.155, p = 0.044). These findings demonstrate that technological access alone is insufficient to ensure sustainable agriculture; instead, sustainability requires the strengthening of agripreneurial mindsets, functional digital literacy, and the effective utilization of climate information for climate-resilient decision-making. Policy implications emphasize prioritizing agripreneurship capacity-building and strengthening institutional facilitation rather than merely increasing the number of farmer groups.